ANALISIS SISTEM PENGENDALIAN INTERNAL DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA JAYAPURA - Mandaku, Vejline Christine (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
This study aims to determine the influence of the internal control system and organizational commitment on the quality of financial statements of the local government of Jayapura City. The type of research used in this study is using quantitative methods. The sampling technique in this study used purposive sampling techniques with a sample of 50 people.The research instrument is in the form of a questionnaire. The results of this test prove that simultaneously the Internal Control System and Organizational Commitment affect the Quality of the Financial Statements of the Local Government of Jyapura City. And partially, Internal Control System Variables and Organizational Commitment Variables affect the Financial Statement Quality Variables.Â Keywords: Internal Control System, Organizational Commitment and Quality of Financial Statements.